MUSYTAQ DALAM BAHASA ARAB; ANALISIS FILOSOFIS MENURUT M. SYAHRUR - Chamzawi, Chamzawi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2007)
This paper discusses the base forms of Arabic words in Syahrur’s perspective. Syahrur argues that the base forms of Arabic words result from fi’il amr (imperative form), not from fi’il madhi (past tense form) as what Ulama’s Kufah stated, and also not from isim mashdar as what Ulama’ Bashrah argued. Syahrur’s opinion cannot be separated from his philosophy concerning the fact that Moslems have still left behind by the other religious communities. The study has implications for both linguistic theory and the socio-cultural discourse on Islamic reform. It encourages scholars to revisit classical linguistic assumptions and explore how language can serve as a tool for societal transformation. Furthermore, it sheds light on the intersection of linguistic analysis and philosophical thought, demonstrating how language can be both a reflection of and a catalyst for cultural progress.